Syair Gulung Ketapang: Sebuah Kajian Lévi-Strauss - Yeni Yulianti; Prima Duantika (tuahtalino, 2016)
This study, entitled “Syair Gulung Ketapang: A Literary Study of Lévi-Strauss. Based of understanding that poetry as a cultural product, according to Lévi-Strauss, the cultural phenomenon can be seen as a linguistic phenomenon with the reason; 1) the language used by a society is regarded as a reflection of the overall culture of the people concerned; 2) because the language part of the culture, or language is one element of culture, and 3) that language is the condition of the culture. It applies qualitative descriptive method with the technique of interview data collection, recording, and literature, and then analyzed using the approach of Lévi-Strauss's structuralism. In brief, the study found that Syair Gulung Ketapang show the uniqueness of the region of origin in the lyrics, then the principle of distinctiveness is finally refers to the emergence of a particular culture. Syair Gulung Ketapang as a language product is recognized to be an important material forming the culture itself.